Three-phase equilibrium based reactive compensation method for submerged arc furnace - LAN ZHENBO; LIU BO; ZHOU QIANG; YAO XIANGYU (2015)
The invention relates to a three-phase equilibrium based reactive compensation method for a submerged arc furnace. The reactive compensation method comprises the following steps of: 1, dividing a load at en electrode end of the submerged arc furnace into a positive sequence load and a negative sequence load, and dividing the three-phase impendence of the load into three-phase balanced impendence and unbalanced impendence; 2, dividing a reactive compensation device of the submerged arc furnace into a positive sequence compensation network and a negative sequence compensation network; 3, obtaining compensation capacity capable of comprehensively compensating a positive sequence reactive component and a negative sequence reactive component of the load; 4, calculating to obtain corresponding active power and reactive power by positive sequence and negative sequence active/reactive power algorithms of the load; and 5, obtaining reactive compensation amount required for each phase of a main circuit of a submerged arc furnace system. By the reactive compensation method, the problem of three-phase current non-equilibrium of a secondary side of the submerged arc furnace system during running can be solved better.